(untitled) (Stato, Chiese e pluralismo confessionale, 2016)
Il contributo, non sottoposto a valutazione, riproduce l’intervento al Convegno “Nutrire l’anima. Cibo, diritto e religione”, promosso dal Dipartimento di Scienze giuridiche "Cesare Beccaria" dell’Università degli Studi di Milano in collaborazione con il Centro Judaica Goren Goldstein (Milano, 17 settembre 2015). SOMMARIO: 1. Premessa – 2. Cibo e trasformazioni del religioso – 3. “Cibo religioso” e mercato – 4. “Cibo religioso” e diritti statuali – 5. Alcune osservazioni conclusive. ABSTRACT: Food, Law, Religion. Religious Freedom Issues in a Global Society The paper focuses on the contemporary relevance acquired by “religious food” and, in particular, on the relationship of this latter with freedom to religion. An overview of the topic of “religious food” highlights transformations of both religious communities and state legal orders and reveals the different role played and methods followed by different rights – the right to a free market and to religious freedom – in the protection of “religious practices”. The tension between a “neutral” commercial approach and a more institutional and religiously-oriented one seems to be a historical constant and still the main characteristic of this question.